Manajemen Induk Organisasi Cabang Olahraga Bola Tangan Kabupaten Kendal Tahun 2020 (Indonesian Journal for Physical Education and Sport, 2022)
The purpose of the study was to determine the parent management of the handball sports organization in the ABTI Regency of Kendal Regency in 2020. The approach in this study used a qualitative descriptive approach. The research subjects are administrators and trainers. Data collection techniques used are observation, interviews, and documentation. Qualitative data analysis uses 3 stages, namely data reduction, data presentation, and drawing conclusions. The results of the research on the Main Management of the Handball Sports Branch in the ABTI Regency of Kendal Regency obtained data that in the first management function planning (planning) as a whole has not gone well because not all members know the vision, mission, and goals and there are still shortcomings in carrying out individual work. The second management function of organizing (organizing) its implementation has not gone well and needs to be improved again by increasing the number of administrators or coaches to support the smooth organization of handball sports in the ABTI Regency Kendal Regency. The third function is leadership (leading) in this case the implementation of the training program has not been going well and in accordance with the program that has been made. The fourth management function is the monitoring (controlling) of the Kendal Regency ABTI Regency organization that has not been running well, it needs to be improved again.